Pengaruh Pemberian Dosis Pupuk Urea terhadap Pertumbuhan Tanaman Bayam Cabut Putih (Amaranthus tricolor L.) - KOGOYA, TINA; DHARMA, I PUTU; SUTEDJA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Effect Of Urea Fertilizer Dosage On The Growth Of Spinach Plants Remove White (Amaranthus tricolor L.) Giving nutrient into the soil is very important for the growth of plants. This study aims to find out the appropriate dosage of urea fertilizer to increase the growth of spinach plants, so that can boost the production of white spinach. This research was conducted on July 12th until the date of August 09th 2017, in experimental garden of Faculty of Agriculture Udayana University. This study used a randomized block design (RAK), the treatment given was a dosage of urea fertilizer consisting of seven treatment level and four replications. Parameters observed and analyzed were plant height, number of leaves, leaf area each plant, root length, fresh weight of plant and dry weight of plant. Before planting the soil samples were analyzed in the laboratory of the Udayana University Faculty of Agriculture to find out the N content in the soil to be used in this study. The results showed that the application of real urea fertilizer can increase the growth of white spinach plant. The highest growth was obtained at the dosage of 0.9 g urea/polybag (U3) with average dry weight of 3.98 g / plant or increased by 437,83% compared to control which yield 0.74 g/plant.